Hubungan Regulasi Diri dan Dukungan Orang Tua dengan Prokrastinasi Mahasiswa Fakultas Dakwah dan Komunikasi UIN Sumatera Utara - Atikah Asna; Munir Abdul; Lahmuddin Lubis (Universitas Medan Area, 2021)
The purpose of this research is to find out: The relationship between self-regulation and parental support with academic procrastination of students from the faculty of da'wah and communication at UIN North Sumatra. The population in this study were 60 students Procrastination from the faculty of da'wah and communication at UIN North Sumatra. The number of samples used in this study were 60 Student. Data collection techniques by means of a scale method that is the scale of self regulation, scale of parental support and scale of procrastination, where previously the three scales were tested on 30 student, with the sampling technique was total sampling. The analysis of this research is multiple regression. The results of the study are a). There is a negative self regulation and parental support with procrastination, this is indicated by the correlation coefficient (R) = 0.625 and sig F change of 0,05, where sig 0.05, it can be concluded that the variable self regulation and parental support variables together or simultaneously related to procrastination variables.. b). There is a significant negative self regulation with procrastination of students from the faculty of da'wah and communication at UIN North Sumatra with a correlation coefficient rx1y = 0.338; sig 0.05; and effective contribution weight of 11,4%. c). There is a significant negative parental support and procrastination, with the correlation coefficient rx2y = 0.336; sig 0.05; with an effective contribution weight of 11,3%. the total effective contribution of the two independent variables on procrastination is 39.0%. d). From these results it is known that there are still 61.0% influence of other factors on Procrastinasi. It is known that the research subjects have relatively high self-regulation and high parental support, while procrastination is also classified as moderate. Based on the results of this study, the hypothesis proposed was accepted.